Penerapan metode teach-back terhadap self-care pasien gagal jantung - Aminah, Siti; Jumaiyah, Wati; Latipah, Siti; Rayasari, Fitrian; Anggraini, Dewi (Holistik Jurnal Kesehatan, 2025)
Background: Heart failure is a chronic disease that requires long-term management and active patient involvement in self-care. Non-adherence to medication, diet, and symptom monitoring increases the risk of recurrent hospitalization. The teach-back method is an effective educational approach to ensure patients’ understanding of medical instructions and improve self-care behaviors. Purpose: To analyze the effectiveness of implementing teach-back method-based education on self-care of heart failure patients. Method: This study implemented an Evidence-Based Nursing Practice (EBNP) approach using a one-group pretest–posttest design. The sample consisted of 13 heart failure patients who met the inclusion criteria. The intervention was delivered in three sessions during hospitalization, followed by two educational follow-ups via telephone after discharge. The instrument used to measure self-care was the European Heart Failure Self-care Behavior Scale (EHFScB-9). Data were analyzed using a paired t-test. Results: There was a significant improvement in patients’ self-care scores after the intervention (mean before = 48.49; after = 80.97; p = 0.000). This indicates that the teach-back method effectively enhanced the self-care abilities of patients with heart failure. Conclusion: The teach-back intervention effectively improved self-care among heart failure patients, demonstrating high validity, an applicable educational SOP, and positive patient responses.   Keyword: Heart Failure; Self-Care; Teach-Back Method.   Pendahuluan: Gagal jantung merupakan penyakit kronis yang membutuhkan manajemen jangka panjang dan keterlibatan aktif pasien dalam melakukan perawatan mandiri (self-care). Ketidakpatuhan pasien terhadap pengobatan, diet, dan pemantauan gejala dapat meningkatkan risiko rawat inap berulang. Metode teach-back merupakan salah satu pendekatan edukasi yang efektif untuk memastikan pemahaman pasien terhadap instruksi medis dan meningkatkan self-care. Tujuan: Untuk menganalisis efektivitas penerapan pendidikan berbasis metode teach-back terhadap self-care pasien gagal jantung. Metode: Implementasi Evidence-Based Nursing Practice (EBNP) dengan desain one group pretest post-test. Sampel terdiri dari 13 pasien gagal jantung sesuai kriteria inklusi. Intervensi diberikan dalam tiga sesi selama perawatan dan dilanjutkan dengan dua kali edukasi melalui telepon setelah pasien pulang. Instrumen pengukuran self-care menggunakan European Heart Failure Self Care Behavior Scale (EHFScB-9). Analisis data dilakukan dengan uji paired t-test. Hasil: Terdapat peningkatan signifikan skor self-care pasien setelah intervensi (mean sebelum 48.49; sesudah 80.97; p = 0.000). Hal ini menunjukkan bahwa metode teach-back mampu meningkatkan kemampuan perawatan mandiri pasien gagal jantung secara bermakna. Simpulan: Intervensi teach-back efektif meningkatkan self-care pasien gagal jantung dengan validitas tinggi, SPO edukasi aplikatif, dan respon positif pasien.   Kata Kunci: Gagal Jantung; Metode Teach-Back; Self-Care.